2014
DOI: 10.1108/ijlm-10-2012-0111
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of stakeholder pressure and knowledge management on supply chain risk and demand responsiveness

Abstract: Purpose – The purpose of this paper is to contribute to the supply chain risk management literature by examining how stakeholders place pressure on the firm to engage in risk management activities. Design/methodology/approach – This paper utilizes a survey approach to test the nomological model. The analysis was carried out using structural equation modeling techniques. Findings –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 66 publications
0
64
0
1
Order By: Relevance
“…Previous research has claimed that if risks are perceived differently, it becomes problematic to share them across partners, and ultimately, to fully identify and implement equally effective mitigation strategies across the whole supply chain (Sitkin and Weingart, 1995, Sheffi, 2001, Jüttner, 2005, Rice and Spayd, 2005, Williams et al, 2008, E. Cantor et al, 2014. This phenomenon is also observed in studies related to supply chain security risks.…”
Section: Summary Of Literaturementioning
confidence: 91%
See 2 more Smart Citations
“…Previous research has claimed that if risks are perceived differently, it becomes problematic to share them across partners, and ultimately, to fully identify and implement equally effective mitigation strategies across the whole supply chain (Sitkin and Weingart, 1995, Sheffi, 2001, Jüttner, 2005, Rice and Spayd, 2005, Williams et al, 2008, E. Cantor et al, 2014. This phenomenon is also observed in studies related to supply chain security risks.…”
Section: Summary Of Literaturementioning
confidence: 91%
“…In a more recent study, it has been found that risk perceptions may also differ depending on firms' stakeholders engagement and thereby influence decisions and responsive behaviors (E. Cantor et al, 2014). Hence, researchers agree on the necessity of common understanding of supply chain risks and coordinated approaches amongst supply chain members (Jüttner et al, 2003, Ijioui et al, 2008, Manuj and Mentzer, 2008b, Pfohl et al, 2010.…”
Section: Unequal Perceptions Of Risks and Effectiveness Of Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk mitigation orientation is defined as the supply chain manager's motivation to implement risk mitigation programmes. It is adapted at the individual level from scales by Kocabasoglu, Prahinski, and Klassen (2007) and Cantor et al (2014). We utilised two control variables in our model.…”
Section: Dependent Independent and Control Variablesmentioning
confidence: 99%
“…Cantor et al [36] showed the positive role of KM in supply chain risk mitigation. Diaz and Bailey [37] proposed the use of a defined KM framework for inventory control and identify and assess risks associated with this inventory and demand.…”
Section: Knowledge Managementmentioning
confidence: 99%